Analisis Kemampuan Metakognisi Siswa dalam Pemecahan Masalah Menggunakan Soal TIMSS ditinjau dari Perbedaan Gender - Siti Nur Fatima; Zainul Munawwir; Lisma Dian Kartika Sari (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
Seeing the differences in the results of several previous studies on metacognitive abilities in problem solving, researchers are interested in examining students' metacognitive abilities in problem solving in terms of gender differences. This problem is important to study because it aims to determine the implementation of the metacognitive abilities of male and female students in problem solvingThe purpose of this study was to determine the metacognitive ability of male and female students in problem solving using TIMSS questions at SMP Al-Falah Pesanggrahan Jangkar for the 2020/2021 academic year. This type of research is descriptive qualitative. The subjects of this study were one male student and one female student from class VII SMP AL-Falah Pesanggrahan who had the same mathematical ability. Data collection techniques in this study were interviews, mathematical ability tests and TIMSS questions. Data analysis in this study was analyzed on each data collection technique. The results of data analysis showed that there was no difference in metacognitive ability in problem solving between male and female students. The metacognitive abilities of male and female students have been used well in problem solving. Both of them can explain their thinking process in every stage of problem solving. Keywords: Metacognition Ability, Problem solving, TIMSS questions, Mathematical Ability, Gender Difference.